Improving the Teaching of Foreign Languages through Comparative Analysis of Images in Proverbs and Sayings - Alla K. Belousova; Nina K. Epritskaya (National Research Mordova State University, 2018)
Introduction. The paper considers the teaching methodology aiding to improve the foreign language acquisition at a technical non-linguistic university by introducing a system of language skills building exercises such as analysis and comparison of images contained in English and Russian proverbs and sayings. The authors consider these techniques as learning and developmental tools. The aim of the study is to describe the above didactic techniques. Relevant research is few. The available practical methodological results are non-systematized. Materials and Methods. The information about the approaches was drawn on 63 sources and generalized. In the linguistic part the authors used the semantic analysis of images, the method of comparison; in the psycho-pedagogical part - the method of psychological-pedagogical experiment. The approbation of techniques was implemented at National Research Irkutsk Technical University in 2017-2018. The objects of the study were represented by 4 groups of first year students (2 experimental and 2 control groups). Results. Firstly, analysis and comparison of semantic images of English and Russian versions of proverbs and sayings helps students of non-linguistic universities to develop their speaking skills. Secondly, the integrative approach develops skills for selecting figurative analogues and contributes to the intelligent use of proverbs and sayings in oral speech. The empirical study proved the adequacy of the authors' approach. This is a new insight into the problem of potentiality of idioms in the development of foreign language speaking abilities. Discussion and Conclusion. The study conducted with participation of university students works towards improvement of teaching methodology essential for teaching foreign languages based on the psychological- deductive approach. The approach may be applied in teaching students of linguistic universities and schoolchildren. This paper addresses foreign language teaching staff concerned with getting familiar with advanced methodologies.